Attitudes of rural upper secondary school students towards learning English as a second language (ESL) in Sarawak / Noraine Jamil - Jamil, Noraine (2015)
In particular, the study was designed to investigate and explore rural upper secondary students' attitudes towards learning English as a second language with regards to the contents of the attitude, context and individual variable in Sarawak. In addition, the study also sought to explore the relative significance of the language attitudes thus identified. Mixed- method was chosen with the implementation of cross-sectional survey and semi structured interviews. Cluster sampling set out with a total of 70 Form 4 students from 3 selected rural secondary schools in Sarawak. Data obtained was analysed by using SPSS software while the interviews were transcribed to refine the findings. The findings from this study indicated that the students have an excellent knowledge on the importance of English language even though they agreed that their mother tongue/ first language interfere when they speak English. In addition, study also discovered the relative significance of the language attitudes thus identified as the result indicated that the irregular use of English also related to the uncertainty of the thoughts about learning English as a second language. Keywords: Attitude; Rural; Upper secondary students; ESL